2014
DOI: 10.1073/pnas.1308650111
|View full text |Cite
|
Sign up to set email alerts
|

In vivo X-ray cine-tomography for tracking morphological dynamics

Abstract: Scientific cinematography using ultrafast optical imaging is a common tool to study motion. In opaque organisms or structures, X-ray radiography captures sequences of 2D projections to visualize morphological dynamics, but for many applications full four-dimensional (4D) spatiotemporal information is highly desirable. We introduce in vivo X-ray cine-tomography as a 4D imaging technique developed to study real-time dynamics in small living organisms with micrometer spatial resolution and subsecond time resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 35 publications
0
58
0
Order By: Relevance
“…The first two requirements listed above, and to some extent also the third, are matched by the commercially available pco.Dimax (PCO AG, Germany; https://www.pco.de) fast CMOS detector, which since its introduction in 2008 has enabled many of the spectacular achievements in fast synchrotron-based imaging (Baker et al, 2012;Rack et al, 2013;dos Santos Rolo et al, 2014;Mokso et al, 2015;Finegan et al, 2015;Maire et al, 2016). The use of the pco.Dimax for the investigation of a large number of more complex dynamic phenomena has, however, been hindered so far by two main technical limitations.…”
Section: Prerequisitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first two requirements listed above, and to some extent also the third, are matched by the commercially available pco.Dimax (PCO AG, Germany; https://www.pco.de) fast CMOS detector, which since its introduction in 2008 has enabled many of the spectacular achievements in fast synchrotron-based imaging (Baker et al, 2012;Rack et al, 2013;dos Santos Rolo et al, 2014;Mokso et al, 2015;Finegan et al, 2015;Maire et al, 2016). The use of the pco.Dimax for the investigation of a large number of more complex dynamic phenomena has, however, been hindered so far by two main technical limitations.…”
Section: Prerequisitesmentioning
confidence: 99%
“…Around the year 2005 (Lambert et al, 2007) the scan time for a single tomographic volume was of the order of 10 min at a spatial resolution of 5-10 mm. Already then, it was, however, demonstrated that it was possible to acquire a tomogram in less than a minute (Di Michiel et al, 2005;Lambert et al, 2010), and today 20 tomographic scans may be acquired within 1 second (Mokso et al, 2013;dos Santos Rolo et al, 2014;Maire et al, 2016). With such an acquisition speed, a new set of challenges arose.…”
Section: Introductionmentioning
confidence: 99%
“…However, volumetric assessments of particular organs in vivo have to be performed carefully as this technique can detect changes through time (e.g., several seconds) (Postnov et al., 2002; Westneat et al., 2008), which could cause measurement errors caused by variation in volume of structures due to normal physiological functions, such as ventilation and digestion. On the other hand, techniques for study real‐time dynamics (termed cine‐tomography) are being made available for 4D analysis (Rolo, Ershov, van de Kamp, & Baumbach, 2014). …”
Section: Application Of X‐ray Computed Tomography In Ecological Studiesmentioning
confidence: 99%
“…In particular, in vivo elucidations of internal processes on short time scales benefit from highest possible volume-acquisitions rates. Exemplarily, this was pointed out by investigation of a moving screw-and-nut-type hip joint [1] in the insect Sitophilus granarius (grain weevil) [2]. Moreover, dose reduction is an issue of key importance in all X-ray imaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…In solving problem (3) in the exact sense of problem (2) the minimum x * (λ ) would have to be inserted into the TV minimisation condition to yield the optimal value λ * by algebraic inversion. As a consequence, x * (λ * ) solves problem (2). To proceed like this, however, is impractical and could even be impossible since (i) the determination of λ * requires an iterative approach, e.g., Newton's method, (ii) λ * is usually not unique implying the need for manual selection, and (iii) a solution in this sense may not exist at all for inconsistent data.…”
Section: Introductionmentioning
confidence: 99%